(untitled) (Al-Mukhtar Journal of Legal Science, 2025)
The constituent authority enjoys broad powers when drafting a new constitution. It can abandon an existing political system and adopt the economic approach it deems appropriate for society. The original constituent authority is extralegal in nature, which explains why it is not subject to any legal basis, given that it is established during periods of legal vacuum. Despite the spread of democratic ideas in the modern era, which advocate that sovereignty resides in the people or the nation, the truth of the ideas put forward regarding the definition of the holder of constituent authority cannot be denied and cannot be refuted in practice. This means that the constituent authority is not restricted to these methods. In other words, it is possible to use any of these methods, or it is possible to combine them, or to use a description that has not been used before